Generational Differences: Generations of Western Society, Managing Multiple Generations in the Workplace - Andrzej Klimczuk (The Encyclopedia of Diversity and Social Justice, 2015)
Generational differences in societies are characteristics generally attributed to people's age that constitute a sociocultural phenomenon. Divisions in the generations differ across nations and extend even to civilizations. Perception and recognition of the different characteristics of each generation affect the cooperation between people in social, political, and economic capacities, and subsequently extend to entities in the public, informal, commercial, and nongovernmental sectors. From the perspective of social justice, it is important to draw attention to how workplace management techniques are used to promote equal opportunities among representatives of various generations.
Keywords: J14; J62; J68; 300; Generational Differences; Generations In the Workplace; Generations of Western Society; Multiple Generations in the Workplace